Removal of an incarcerated intrauterine device reaching the serosal surface of the uterus by hysteroscopy alone: a case report - You, Min; Chen, Qin-Fang; Lu, Hai-Qian (Frontiers in Medicine, 2025)
BackgroundAn intrauterine device (IUD) is a widely used long-term contraceptive device for family planning. However, the IUD can lead to various complications. Severe complications and remedial measures caused by IUDs have been reported in the literature; however, detailed surgical approaches for safely removing the IUD within the minimum surgical range have rarely been described especially in postmenopausal women. Therefore, this article aims to share our surgical experience in removing an IUD that had reached the serosal surface of the uterus using hysteroscopy alone after menopause to provide new clinical ideas.Case introductionWe report the case of a 63-year-old Chinese patient with a 12-year history of menopause. She had an IUD placed after an abortion more than 30 years ago. She came to the hospital because of occasional a small amount of unprovoked vaginal bleeding, the preoperative examination suggested an embedded IUD that appeared to have reached the serosal surface of the uterus. The IUD was not visible during hysteroscopic surgery because of uterine adhesions. Microscissors were employed to cut along the white adhesion band, revealing a faintly visible metal wire. We successfully removed the IUD using hysteroscopy only. The patient has recovered well after surgery and has been in good health for more than 5 months, with no complaints of abdominal pain or vaginal bleeding.ConclusionThis case suggests that hysteroscopic exploration can be performed in patients whose preoperative examination indicates that the IUD has reached or protrudes from the serosal surface of the uterus. If necessary, laparoscopic or open surgery can be performed. For patients whose IUD is not visible in the uterine cavity, preoperative imaging can help assess the thickness of the uterine myometrium and the distance to the serosal surface. Intraoperatively, scissors can cut through tissue or adhesions, and instruments can measure the separation distance or visualize the device within the adhesions. In addition, it is crucial to know the patient’s expectations, assess the pros and cons, and discontinue the procedure if necessary.